Smart Farming Automatic Irrigation System Berbasis Iot Dalam Optimalisasi Suplai Air Lahan Pada Perkebunan Di Desa Pondok Meja: Smart Farming Automatic Irrigation System Berbasis Iot Dalam Optimalisasi Suplai Air Lahan Pada Perkebunan Di Desa Pondok Meja - Pebriani Daulay, Diana; Yogi; Ridho Tri Rokhandi (Politeknik Aceh, 2024)
The use of agricultural land in Pondok Meja Village has the potential to implement an automatic irrigation system based on the Internet of Things (IoT) to optimize water supply and support sustainable agriculture. This village is facing the problem of climate change which affects water availability and the practice of watering plants which is still done manually, as well as the community's lack of knowledge about IoT-based automatic irrigation technology. An automatic irrigation system using IoT can monitor and regulate soil moisture in real-time, which is very important for dragon fruit plants which require humidity between 70% and 90% to grow optimally. This technology works by automatically controlling the water pump to maintain soil moisture, using devices such as Arduino Uno R3, soil moisture sensor, water pump, relay module, 16x2 LCD, and jumper cables. The application of this technology aims to increase the efficiency of water use, as well as enable farmers to make more informed decisions in irrigation and plant care. Implementation of this system has been proven to not only increase water efficiency, but also contribute to increased crop yields and land health, making it an effective solution to modern agricultural challenges.